Causal association of blood cell traits with inflammatory bowel diseases: a Mendelian randomization study - Zhang, Fangyuan; Jiang, Feiyu; Yao, Ziqin; Luo, Hongbin; Xu, Shoufang; Zhang, Yingying; Wang, Xinhui; Liu, Zhiwei (Frontiers in Nutrition, 2024)
Background Observational studies have found associations between blood cell traits and inflammatory bowel diseases (IBDs), whereas the causality and dose-effect relationships are still undetermined. Methods Two-sample Mendelian randomization (MR) analyses using linear regression approaches, as well as Bayesian model averaging (MR-BMA), were conducted to identify and prioritize the causal blood cell traits for Crohn’s disease (CD) and ulcerative colitis (UC). An observational study was also performed using restricted cubic spline (RCS) to explore the relationship between important blood cell traits and IBDs. Results Our uvMR analysis using the random effects inverse variance weighted (IVW) method identified eosinophil (EOS) as a causal factor for UC (OR = 1.36; 95% CI: 1.13, 1.63). Our MR-BMA analysis further prioritized that high level of lymphocyte (LYM) decreased CD risk (MIP = 0.307; θ^MACE = −0.059; PP = 0.189; θ^λ = −0.173), whereas high level of EOS increased UC risk (MIP = 0.824; θ^MACE = 0.198; PP = 0.627; θ^λ = 0.239). Furthermore, the observational study clearly depicts the nonlinear relationship between important blood cell traits and the risk of IBDs. Conclusion Using MR approaches, several blood cell traits were identified as risk factors of CD and UC, which could be used as potential targets for the management of IBDs. Stratified genome-wide association studies (GWASs) based on the concentration of traits would be helpful owing to the nonlinear relationships between blood cell traits and IBDs, as demonstrated in our clinical observational study. Together, these findings could shed light on the clinical strategies applied to the management of CD and UC.